Peer acceptance of female students in private schools: study of differences in peer acceptance by gender - Rozi Sastra Purna; Izzanil Hidayati; Abdur Rahman; Puti Dewi Sartika; Fitri Angraini (Jurnal Psikologi Tabularasa, 2023)
This study aims to determine the difference in peer acceptance based on gender of private junior high school students in the city of Padang, West Sumatra Province, Indonesia. The number of subjects involved in this study were 146 private junior high school students consisting of 73 male and 73 female students. The sampling technique in this study used cluster sampling which was taken based on the sub-districts in the city of Padang. Peer acceptance of students is measured using a peer acceptance scale. The results of this study are that there are differences in peer acceptance between male students and female students which indicates that female students have a higher level of peer acceptance than male students. Female and male students had the highest peer acceptance aspect scores on validation and caring aspects (mean=23.59 and mean=21.53). The lowest aspect score for female students was intimate exchange (mean=20.51), while the lowest aspect for male students was conflict and betrayal (mean=18.12).Penelitian ini bertujuan untuk mengetahui perbedaan peer acceptance siswa SMP Swasta kota Padang berdasarkan jenis kelamin. Jumlah subjek yang terlibat pada penelitian ini adalah sejumlah 146 siswa SMP Swasta yang terdiri dari laki-laki 73 orang dan perempuan 73 orang. Teknik pengambilan sampel dalam penelitian ini menggunakan cluster sampling yang diambil berdasarkan kecamatan yang ada di kota Padang. Peer acceptance siswa diukur dengan menggunakan peer acceptance scale. Hasil penelitian ini menunjukkan bahwa terdapat perbedaan peer acceptance antara siswa laki-laki dan siswa perempuan Sekolah Menengah Pertama Swasta di kota Padang. Siswa perempuan memiliki tinggat peer acceptance yang lebih tinggi daripada siswa laki-laki. Siswa perempuan dan laki-laki memiliki skor aspek peer acceptance tertinggi pada aspek validation and caring (mean=23,59 dan mean=21,53), skor aspek terendah pada siswa perempuan adalah intimate exchange (mean=20,51), dan siswa laki-laki memiliki aspek terendah pada conflict and betrayal (mean=18,12).